WhatsApp in language classroom: Gauging Saudi EFL teachers’ roles and experiences - Fahd Hamad Alqasham, Arif Ahmed Mohammed Hassan Al-Ahdal, (Opción, 2020)
The current study used primary data to evaluate teachers' agency from a dialogical perspective that utilizes WhatsApp (WA) to bring innovation into a Saudi EFL classroom via comparative research methods. The findings of the study showed that the use of WhatsApp outside the English classroom created conducive opportunities for students to develop independence, practice what they read, work together and switch from being passive learners to active ones. The study concludes that EFL teachers in the Saudi context are positively disposed towards adopting an active role of agency encouraging dialogical perspective via WA.